2003
DOI: 10.1021/jo0206871
|View full text |Cite
|
Sign up to set email alerts
|

Practical and High-Yield Syntheses of Dihydromorphine from Tetrahydrothebaine and Efficient Syntheses of (8S)-8-Bromomorphide

Abstract: A practical method for the conversion of tetrahydrothebaine to dihydromorphine in 92% yield is described. The procedure should allow more efficient production of opium products and may be easily modified for large-scale synthesis. The conversion of codeine to (8S)-8-bromomorphide, a potentially valuable intermediate to 6-demethoxyoripavine and derivatives, is also described. The absolute configuration of (8S)-8-bromomorphide was determined by a single-crystal X-ray diffraction study of the hydrobromide salt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…(4R,4aR,7S,7aR,12bS)-7-(Benzylamino)-3-methyl-2,3,4,4a,5,6,7,7a-octahydro-1H-4,12-methanobenzofuro[3,2-e]isoquinolin-9-ol ( 26 ). To a solution of hydromorphone [ 31 , 32 ] (2.28 g, 8.0 mmol) in DCE (60 mL) was added benzylamine (0.96 mL, 8.8 mmol, 1.1 equiv), acetic acid (0.91 mL, 16.0 mmol, 2 equiv), and NaBH(OAc) 3 (2.54 g, 1.2 mmol, 1.5 equiv), respectively. The mixture was stirred at room temperature for 24 h. Water (20 mL) was added to the reaction mixture, and it was basified to a pH ~8 with 28% NH 4 OH.…”
Section: Methodsmentioning
confidence: 99%
“…(4R,4aR,7S,7aR,12bS)-7-(Benzylamino)-3-methyl-2,3,4,4a,5,6,7,7a-octahydro-1H-4,12-methanobenzofuro[3,2-e]isoquinolin-9-ol ( 26 ). To a solution of hydromorphone [ 31 , 32 ] (2.28 g, 8.0 mmol) in DCE (60 mL) was added benzylamine (0.96 mL, 8.8 mmol, 1.1 equiv), acetic acid (0.91 mL, 16.0 mmol, 2 equiv), and NaBH(OAc) 3 (2.54 g, 1.2 mmol, 1.5 equiv), respectively. The mixture was stirred at room temperature for 24 h. Water (20 mL) was added to the reaction mixture, and it was basified to a pH ~8 with 28% NH 4 OH.…”
Section: Methodsmentioning
confidence: 99%
“…We studied the demethylation of compound 3 with several reactants in different reaction conditions. Treatment of compound 3 with aqueous hydrobromic acid 30 or hydrobromic acid in acetic acid, 31,32 gave no product. Reaction of compound 3 with boron tribromide 33 (4 and 6 equivalents) in methylene chloride gave the product in 50% yield.…”
Section: Chemistrymentioning
confidence: 99%
“…To prepare the necessary quantity of N-norhydromophone base (S10 in Scheme S1, see Supplementary Material) we used a previously reported efficient process (hydromorphone synthesis, Scheme S1) for the conversion of (−)-tetrahydrothebaine (S1) to dihydromorphine (S3) [28]. We found that using the HCl salt of compound S3 as the reactant instead of the hydrate (product of the basic hydrolysis of S2) could dramatically increase the yield of the oxidation [29], achieving hydromorphone hydrochloride (S4) in 90% yield.…”
Section: Chemistrymentioning
confidence: 99%